Development of Creative Problem Solving-Based Physics Learning Modules to Improve Students' Creative Thinking Skills - Siti Maryam Ulfa; M. Sidin Ali; Khaeruddin (Jurnal Penelitian Pendidikan IPA, 2025)
This research is a type of research and development (R&D) with a 4D model This research aims to (i) design the results of the development of a physics learning module based on creative problem solving to improve students' creative thinking skills which are reviewed from a theoretical and empirical point of view, practitioner responses, student responses, and testing the effectiveness of physics-based learning modules creative problem solving. The subjects of this study are class X.1 as an experimental class and class X.2 as a control class. The results of the study show that learning modules developed based on theoretical and empirical validity are recommended to be suitable for use. The results of the analysis of practitioners' and students' responses to the developed modules show very practical criteria. The effectiveness test of the physics learning module based on creative problem solving was analyzed based on the results of the students' posttest. The Effectiveness Test of the learning module uses t-test analysis. From the results of the study, it can be seen that the learning modules developed have a significant (effective) increase based on statistical tests. Thus, there is an influence of the use of learning modules on students' creative thinking skills. Based on the results of this study, it can be concluded that the physics learning module based on creative problem solving is declared valid and effective so that it is suitable for use as a learning resource.